On Almost Binarity in Weakly Circularly Minimal Structures - Kulpeshov, Beibut Shaiykovich (Eurasian Mathematical Journal, 2016)
We prove that \( \aleph_0 \)–categorical non-1-transitive weakly circularly minimal theories of convexity rank 1 are almost binary.